Temporal relationship between successful pancreas transplantation and control of ocular complications in alloxan-induced diabetic rats - Spadella, César Tadeu [UNESP]; Machado, José Lucio Martins [UNESP]; Lerco, Mauro Masson [UNESP]; Ortolan, Erika Veruska Paiva [UNESP]; Schellini, Silvana Artioli [UNESP]; Gregório, Elisa Aparecida [UNESP] (Elsevier B.V., 2008)
Purpose. The impact of pancreas transplantation (PT) on the progression of eye disease is still controversial. This study evaluated the course of retinopathy in transplanted rats in two different diabetic stages.Methods. Sixty inbred male Lewis rats were assigned to four experimental groups: NC-15 nondiabetic control rats; DC-15 untreated diabetic control rats; PT1-15 diabetic rats that received syngeneic pancreas transplants 2 weeks after alloxan diabetes induction; PT2-15 diabetic rats that received pancreas transplants 12 weeks after diabetes onset. Clinical and laboratory parameters and tens opacity were examined in all rats prior to treatment and at 1-, 6-, and 12-months follow-up. Nucleated eyes from five rats in each group processed for ultrastructural study of the retinal at 6 and 12 months after PT or at follow-up.Results. Cataracts were observed in 20%, 60%, and 100% of DC rats at 1-, 6-, and 12-months follow-up, respectively. Early PT (2 weeks) significantly reduced the prevalence of this complication but not late (12 weeks) PT. PT1 rats also showed improved ultrastructure of the superficial and deep capillary plexuses of the retina, and of Muller cells, compared with DC and PT2. In the last group, retinopathy continued to evolve despite successful PT.Conclusion. Our results suggested that prevention of diabetic ocular lesions by PT was closely dependent on earlier performance of the procedure.